From Field to Consumer, The Effect of Indonesian National Team Player Brand Ambassadors on Le Minerale Purchases - Teti Sumarni (Mathematics Education Study Program, 2024)
As changes in modern lifestyles increase the demand for quality products, the bottled drinking water (AMDK) market is experiencing rapid growth, with the global value reaching USD 10.24 billion by 2022. In contrast, the use of bottled water causes other environmental problems, especially plastic waste, which is a major concern for consumers. This study found that there is a lack of understanding of the influence of Le Minerale brand ambassadors, especially Indonesian national team players, on their decision to purchase the goods. This study used a quantitative approach by collecting primary data through questionnaires specific to the Indonesian population who may purchase the product. The results showed that the selected brand ambassadors significantly influenced consumers' decision to purchase the item, with their attractiveness and credibility increasing consumers' interest in purchasing the item. In addition, the emotional connection built between brand ambassadors and customers increases brand loyalty. This study shows that the proper selection of brand ambassadors in a marketing strategy is essential for enhancing brand image and attracting consumer attention